2021
DOI: 10.3390/nu13113860
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Folate and Assessment of the Folate Deficiency Prevalence in Slovenia Using Serum Biomarkers

Abstract: Folate deficiency is associated with various health issues, including anemia, cardiovascular disease, and birth defects. Low folate intake and suboptimal folate status were found in several countries; however, this topic has not yet been investigated in Slovenia. Dietary folate intake and serum folate status were investigated through the nationally representative food consumption study SI.Menu/Nutrihealth. Folate intake was estimated using a sample of N = 1248 subjects aged 10–74 years, stratified in three age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 92 publications
0
12
0
Order By: Relevance
“…Our previous in vivo studies had confirmed that compared with supplementation limited to the periconceptional period, prolonged maternal folic acid supplementation throughout pregnancy was more beneficial to the neurobehavioral development of offspring [8]. Low folate status in early life is linked to the risk of numerous adverse health conditions throughout life, from congenital disabilities to cardiovascular disease, cancer, and cognitive dysfunction in the elderly [1][2][3][4][5][6][7]. However, the impact of folic acid on neurodevelopment is complicated, other than NTDs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our previous in vivo studies had confirmed that compared with supplementation limited to the periconceptional period, prolonged maternal folic acid supplementation throughout pregnancy was more beneficial to the neurobehavioral development of offspring [8]. Low folate status in early life is linked to the risk of numerous adverse health conditions throughout life, from congenital disabilities to cardiovascular disease, cancer, and cognitive dysfunction in the elderly [1][2][3][4][5][6][7]. However, the impact of folic acid on neurodevelopment is complicated, other than NTDs.…”
Section: Discussionmentioning
confidence: 97%
“…It has been conclusively established that folic acid supplementation prior to and during early pregnancy (up to 12 weeks of gestation) can prevent neural tube defects (NTDs). In recent years, low folate status in early life has been linked to the risk of numerous adverse health conditions throughout life, from congenital disabilities to cardiovascular disease, cancer, and cognitive dysfunction in the elderly [1][2][3][4][5][6][7]. However, the impact of folic acid on neurodevelopment is complicated, other than NTDs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the biomarkers of vitamins were not considered. However, previous studies suggested that diet intake was highly correlated with B vitamin status [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Slovenian national dietary survey SI.Menu was conducted in 2017/2018 ( 104 ), and the 2017 edition of the branded foods dataset was used to estimate the nutritional composition of reported foods. This approach has already supported several epidemiological studies, which investigated diet-related-risk factors and population intakes of total/free sugars ( 69 ), dietary fiber ( 70 ), TFAs ( 68 ), vitamin D ( 67 ) and folate ( 71 ).…”
Section: The Exploitation Of Use Of Branded Foods Database In Nutrition Researchmentioning
confidence: 97%
“… List only include studies where Slovenian branded food databases were exploited directly. Food monitoring studies datasets were used for several other studies, for example, to support in the sampling of foods in the food supply for assessment of the content of trans fatty acids in foods ( 64 , 65 ), for assessment of salt iodization ( 66 ), for assessment of dietary intakes ( 67 71 ), food marketing ( 25 , 72 74 ) and offers in vending machines ( 75 , 76 ). Studies exploiting additional Slovenian branded foods composition datasets ( 44 , 66 , 77 79 ) are also not included .…”
Section: The Exploitation Of Use Of Branded Foods Database In Nutrition Researchmentioning
confidence: 99%